Compliance With Msme Taxpayers In Mamajang District - Lenny M. Posumah; Mardiana Ruslan; Rosfianti M. Yadasang; Rosma Ndiak; Irwan Moridu (STIE AMKOP, 2023)
In particular for Mamajang District, this study aims to investigate four factors that can affect MSME taxpayer compliance: taxpayer awareness, tax authorities' services, knowledge and understanding of government regulations on taxation (PP No. 46 of 2018), and knowledge and understanding of taxpayers. 55 MSME respondents who were registered with the Office of Cooperatives, SMEs, and Industry in Makassar City made up the sample. The Isaac and Michael formula is used in the sampling technique, and its error rate is 4%. Multiple linear regression must be used to assess the data, as well as validity and reliability evaluations for research tools. According to the findings, the compliance of MSME taxpayers in the Mamajang District is significantly influenced by taxpayer knowledge and the modernization of the tax administration system. Keywords : Knowledge and Understanding of Government Regulations on Taxation, Taxpayer Awareness, Fiscal Services